Chapter Progettare e realizzare percorsi didattici di Storia della scuola per la primaria con la Public History - Peiretti, Marta (Public History of Education. Teorie, esperienze, strumenti, 2022)
The essay illustrates some basic themes underlying the teaching of history of education in primary school. Some examples of workshops for elementary school students are then illustrated, recently carried out in the School and Children's Book Museum in Turin.